Influencia del acompañamiento familiar en la educación de los niños inclusivos del C.E.B.E Dejad que los niños vengan a mí, Guadalupe 2021 - Crispin Moncada, Anthony David (2023)
The present investigation was carried out with the purpose of analyzing the influence of family accompaniment in the education of inclusive children of the C.E.B.E Let the children come to me, Guadalupe 2021. The sample with which we worked were 30 parents, using a reliable questionnaire to be able to collect information regarding the variables of family support and education of inclusive children. Likewise, to carry out the research, methods such as deductive, phenomenological and statistical were applied, also making use of both qualitative and quantitative techniques, such as the interview and the questionnaire. Instruments such as the interview guide, interview record and questionnaire were used. The results obtained in the present investigation reflect the hypotheses raised, so that family support has a great influence on the education of inclusive children of the C.E.B.E.